Complexidade e relevância de um gesto profissional docente aparentemente simples - Althaus, Dalvane (2013)
This presentation aims to discuss some results of one of the actions of the Continued Teacher‟s Training in Higher Education in progress at UTFPR Pato Branco Campus. At first we present a brief review of the history of continued teacher training in Brazilian Higher Education. The theoretical basis that supports this work is the following: the Bakhtinian theory of dialogic discourse analysis; the Vygotskian theory of human development; and the psychology theory of Clot‟s work. The protagonists of this intervention were two teachers from the Informatics Department of UTFPR Pato Branco Campus. The methodology was of the developmental type and the method used was the simple and crossed self-confrontation, which consists in confronting the teacher with a sequence of his images in class and, from these pictures, in leading him to dialogue and reflect. In order to attempt to understand the conditions under which teacher development occurs, dialogue transcripts of self-confrontations were analyzed. The transcription was performed according to the NURC-SP project standards. In the produced documentation, an analysis of dialogic discourse was performed in order to verify if teacher‟s development occurs and, if so, in order to establish how teacher‟s development occurs by using language. We note that it is difficult for teachers to do their work: the teacher's desk is low, which leads to a conflict: to perform teacher‟s work while sitting or standing? While standing, the teacher must stoop to type and this may damage his/her physical health. While sitting, the teacher loses contact with students and it brings about situations of indiscipline, which may damage his/her mental health. In order to make a contribution to solving this problem, we are developing - in partnership with teachers - a table for notebook with adjustable height, so that teachers can do their work while standing, without damaging their health. The teacher who chooses to type while inclined, even if he damages his health, shows well developed stylistic recreation. His engagement leads him to make every effort to do his work with excellence. The teacher who prefers to work while seated faces difficulties which he tries to overcome and cannot find a way to recreate his style. By observing his images in the classroom, he realizes what he is like and how he can do his job differently. The teacher who faces difficulties is led to an awareness through self-confrontation and dialogue. The gesture of performing the teaching work while standing may seem simple and perhaps insignificant, but – when analyzed in its essence – reveals its complexity and relevance.